2019
DOI: 10.5194/angeo-37-405-2019
|View full text |Cite
|
Sign up to set email alerts
|

Evanescent acoustic-gravity modes in the isothermal atmosphere: systematization and applications to the Earth and solar atmospheres

Abstract: Abstract. The objects of research in this work are evanescent wave modes in a gravitationally stratified atmosphere and their associated pseudo-modes. Whereas the former, according to the dispersion relation, rapidly decrease with distance from a certain surface, the latter, having the same dispersion law, differ from the first by the form of polarization and the nature of decrease from the surface. Within a linear hydrodynamic model, the propagation features of evanescent wave modes in an isothermal atmospher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 29 publications
0
2
0
5
Order By: Relevance
“…which are usually used to consider both acoustic and gravity waves [1,48], as well as evanescent waves [32,38,39]. Note the horizontal anisotropy of wave propagation, namely, the dependence of the form of equations ( 5) -( 7) on the direction of wave propagation.…”
Section: Initial Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…which are usually used to consider both acoustic and gravity waves [1,48], as well as evanescent waves [32,38,39]. Note the horizontal anisotropy of wave propagation, namely, the dependence of the form of equations ( 5) -( 7) on the direction of wave propagation.…”
Section: Initial Equationsmentioning
confidence: 99%
“…The role of evanescent waves in the dynamics and energy of atmospheric processes has been studied to a much lesser extent. Until recently, only a few solutions were known for evanescent modes: the Brunt-Väisälä oscillation ( [32]), the Lamb wave [35,36], the f-mode [37], and the γ-mode [38]. However, in [39] it was shown that the spectrum of evanescent acoustic-gravity waves is continuous.…”
Section: Introductionmentioning
confidence: 99%
“…Ðîëü åâàíåñöåíòíèõ õâèëü â äèíàì³ö³ òà åíåðãåòèö³ àòìîñôåðíèõ ïðîöåñ³â âèâ÷åíà çíà÷íî ìåíøîþ ì³ðîþ. Äî íåäàâíüîãî ÷àñó áóëî â³äî ìî ëèøå ê³ëüêà ðîçâ'ÿçê³â äëÿ åâàíåñöåíòíèõ ìîä: êîëèâàííÿ Áðåí òà -Âÿéñÿëÿ [49]), õâèëÿ Ëåìáà [4,28], f-ìîäà [23], à òàêîae g-ìîäà [9]. Îäíàê â ðîáîò³ [10] áóëî ïîêàçàíî, ùî ñïåêòð åâàíåñöåíòíèõ àêóñòèêî-ãðàâ³òàö³éíèõ õâèëü º íåïåðåðâíèì.…”
Section: âïëèâ îáåðòàííÿ àòìîñôåðè çåìë³ íà ñïåêòð àêóñòèêî-ãðàâ³òàö³...unclassified
“…ÿê³ çàçâè÷àé âèêîðèñòîâóþòüñÿ ÿê äëÿ ðîçãëÿäó àêóñòè÷íèõ ³ ãðàâ³òà -ö³éíèõ õâèëü [20,45], òàê ³ åâàíåñöåíòíèõ õâèëü [9,10,49]. ³äçíà÷èìî ãîðèçîíòàëüíó àí³çîòðîï³þ ïîøèðåííÿ õâèëü, à ñàìå çàëåaeí³ñòü âèäó ð³âíÿíü ( 5)-( 7) â³ä íàïðÿìêó ïîøèðåííÿ õâèëü.…”
Section: âèõ²äí² ð²âíßííßunclassified
“…Якщо не враховувати затухання, то дисперсійне рівняння (6) має бути дійсним, і це накладає певні обмеження на параметр a . Він може бути або дійсним, що відповідає горизонтальним (еванесцентним) хвилям [18,19], або мати вид (1/ 2 ) [10]. Це відповідає вільно поширюваним АГХ, які розповсюджуються під кутом до горизонтальної площини, і найчастіше спостерігаються в земній атмосфері [8,9].…”
Section: T Divv Ttunclassified